Mycobacterial Nucleoside Diphosphate Kinase Blocks Phagosome Maturation in Murine Raw 264.7 Macrophages - Sun, Jim; Wang, Xuetao; Lau, Alice; Liao, Ting-Yu Angela; Bucci, Cecilia; Hmama, Zakaria (PLOS ONE, 2010)
Background Microorganisms capable of surviving within macrophages are rare, but represent very successful pathogens. One of them is Mycobacterium tuberculosis (Mtb) whose resistance to early mechanisms of macrophage killing and failure of its phagosomes to fuse with lysosomes causes tuberculosis (TB) disease in humans. Thus, defining the mechanisms of phagosome maturation arrest and identifying mycobacterial factors responsible for it are key to rational design of novel drugs for the treatment of TB. Previous studies have shown that Mtb and the related vaccine strain, M. bovis bacille Calmette-Guérin (BCG), disrupt the normal function of host Rab5 and Rab7, two small GTPases that are instrumental in the control of phagosome fusion with early endosomes and late endosomes/lysosomes respectively. Methodology/Principal Findings Here we show that recombinant Mtb nucleoside diphosphate kinase (Ndk) exhibits GTPase activating protein (GAP) activity towards Rab5 and Rab7. Then, using a model of latex bead phagosomes, we demonstrated that Ndk inhibits phagosome maturation and fusion with lysosomes in murine RAW 264.7 macrophages. Maturation arrest of phagosomes containing Ndk-beads was associated with the inactivation of both Rab5 and Rab7 as evidenced by the lack of recruitment of their respective effectors EEA1 (early endosome antigen 1) and RILP (Rab7-interacting lysosomal protein). Consistent with these findings, macrophage infection with an Ndk knocked-down BCG strain resulted in increased fusion of its phagosome with lysosomes along with decreased survival of the mutant. Conclusion Our findings provide evidence in support of the hypothesis that mycobacterial Ndk is a putative virulence factor that inhibits phagosome maturation and promotes survival of mycobacteria within the macrophage.